Collinear Terahertz Generation from LiNbO3 Wafer Driven by an Ultrafast Yb-Laser - Kang Wang; Hongyang Li; Zhuorui Zheng; Yi Liu; Ye Tian; Liwei Song (IEEE Photonics Journal)
We propose and experimentally demonstrate a terahertz (THz) source based on optical rectification in lithium niobate wafers driven by an ultrafast ytterbium laser. Terahertz pulses with a repetition of 10 kHz and a spectrum of 0.1∼6 THz are generated via a collinear geometry. The phase-matching condition is analyzed and the effect of crystal thickness is investigated. Our study demonstrates a compact and stable source for terahertz spectroscopy and imaging applications.